(untitled) (International Journal of Geoscience, Engineering and Technology, 2021)
Septic tanks are one of the oldest methodologies for sewage treatment and are, even today, extensively used in all countries of the world as a form of primary treatment of domestic sewage. The bacteria responsible for purifying the effluent in septic tanks are strict anaerobic bacteria and do not survive in the presence of oxygen. Therefore, the objective of this work is to use an Arduino platform to monitor these environmental conditions. Making it necessary to use temperature and pH sensors for the needs and programming of the Arduino platform, adapting it for the use of monitoring specific conditions in a plastic bomb chamber.The materials needed to install the monitoring system are sensors, a module, an Arduino platform, cables and connectors. The monitoring system is easy to read, with interdisciplinary potential, as it makes it possible to determine the temperature and pH values ​​quickly, accurately and with knowledge related to the programming language, microbiology, chemistry and environment, respectively.